Studying Some Electrical Properties for ZnSe Films Prepared by Using the Thermal Evaporation Method in vacuum - Taha, R.Y.; Raouf, A. M. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Thin films of zinc selenide ZnSe have been prepared by using thermal evaporation method in vacuum with different thickness (1000 – 4000) Ao and a deposited on glass substrate and studying some electrical properties including the determination of A.C conductivity and real, imaginary parts of dielectric constant and tangent of loss angle. The result shows that increasing value of A.C conductivity with increasing thickness and temperature, and increasing capacitance value with increasing the temperature and decrease with increasing frequency . Real and imaginary parts of dielectric constant and tangent of loss angle decrease with increasing frequency